Antes eu deixava a vida me levar, agora sou eu quem levo minha vida: sentidos de responsabilização produzidos por adolescentes em cumprimento de medida socioeducativa - Cavalcante, Amanda Lívia de Lima (2019)
This research arose from concerns generated throughout my academic and professional experience with adolescents who committed infraction acts. The question of childhood and adolescence was not always considered an important agenda to society and to State, there being for this part of population a series of violations of rights, mainly what refers to legislation. From social movements, who fought for guarantee children and adolescents' rights, was made and approved in 1990 the Child and Adolescent Statute that, besides regulating what is established in the Federal Constitution about human rights, defines rules to juridical accountability of adolescents who commit infractions, specified by socio-educational measures. Associated with this legislation, more recently, was approved the National System of Socio-Educational Attendance, which establishes the regulation of this attendance, as defined by the Statute, in addition to supervising and guiding the proper execution of the measures. Although we have a specific law to treat juvenile infraction, it was verified that both the Statute and the National System of Socio-Educational Attendance do not elucidate how adolescent author of an infraction act takes responsibility beyond the compliance with the socio-educational measure. In face of that, this dissertative study aimed to analyze the meanings about juvenile accountability produced by adolescents undergoing social-educational measure. To this, the methodological path of this research had a qualitative character, using the procedure of narrative interview (Brunner, 2013) with adolescents who were undergoing socio-educational measure in the Center of Specialized Reference of Social Assistance. Were interviewed, in total, six adolescents undergoing social-educational measure in the said institution and also a thematic workshop was made. The analysis of the corpus of the research was made under a Cultural-Historical perspective, from an interpretative analysis that allowed us to understand the meaning produced by the adolescents who participated in the research about the process of juvenile accountability, besides it made possible a new elaboration of the meanings and senses that they produced about this experience. The meaning of accountability produced by young people was linked to punitive processes, where institutional violence proved to be one of the main interventions disguised as accountability. The final considerations demonstrate that the process of juvenile accountability is not something given in the legislation; it should be constructed with the adolescent in the moment he is undergoing socio-educational measure. For this, it is necessary that the socio-educational system offers a space where the subject can position himself before his experiences in a conscious way so as to elaborate reflections that strengthen his citizenship.